Assessing the Effects of NEP 2020: Undergraduates in Betul District's Knowledge of Yoga and Physical Education - Deeepak Kumar Hatia; Vikash Saxena (International Martial Arts and Culture Journal, 2026)
Every country must update its educational policies, and how these policies are implemented depends on the facilities and resources available for education. With the help of educators and other stakeholders, every aspect of the updated educational policy is successfully implemented at the grassroots level. The study's objective was to educate Betul district undergraduate students about yoga and physical education (in the framework of National Educa. Yoga is a scientific and spiritual practice that simultaneously tackles the psychology, philosophy, and practicalities of conscious evolution. It is an all-encompassing method that unites the body, mind, and spirit by emphasizing balance and attention. Since ancient times, India has had a renowned educational system. The Gurukul method of instruction is well known to all of us. Since independence, there have been some changes made to the Indian educational system. This study used a descriptive survey methodology. The combination of both research approaches is the most effective way in achieving the research objective due to their complementary strengths. Both quantitative and qualitative assessments are known to have certain particular drawbacks. College-bound students from Betul districts made up the study's populations. From the many colleges in the Betul district—Amla, Atner, Bhaisdehi, Ghodadongri, Multai, Sarni, Sahpur, and Betul—a total of 800 students were chosen. The study's conclusions showed that student engagement and participation are poor. The main causes of students' low involvement include the teaching strategies used by instructors, which include lecturing instead of inviting students to participate, lack of confidence, a lack of educational resources, a negative attitude toward the subject, etc. , if the teacher was verbally abusive, the majority of kids would engage and perform well in the physical education classroom. The students indicated that they did not learn the material, but would participate to avoid the repercussions of the teacher. , intrinsically motivated behaviors are engaged in for their own sake, for the pleasure and satisfaction derived from the process of engaging in the activity.